Pelayanan Surat Keterangan Pindah Bagi Penduduk Migran Di Kabupaten Bogor Provinsi Jawa Barat - Hutasoit, Imelda; Madjid, Udaya; Ripa’i, Ahmad; Sri Rejeki, Wiwik Roso (Jurnal Agregasi, 2024)
The Bogor Regency Population and Civil Registration Service has an important role in managing population administration because the number of migrants who need population administration services related to their move is quite high. This research aims to describe population administration services for migrant residents in Bogor Regency and the various factors that influence them. The research method used in this research is Descriptive Qualitative. Data collection was carried out by observation, interviews, and documentation. The data analysis technique is carried out in several stages, namely preparing the data, reading all the data, presenting the data, organizing the data, analyzing the data, describing the data, and making interpretations/drawing conclusions. The results of the research show that in providing population administration services for migrant residents, the Bogor Regency Dukcapil Office has fulfilled the dimensions of good service, fulfilled through various efforts including the One Day Service (ODS) program, the availability of clear Service Standard Operating Procedures (SOP), and use of technology to speed up the service process, as well as create a comfortable and efficient environment for migrant residents processing population documents.